Bioelectronic Interfaces: Soft, Implantable Bioelectronic Interfaces for Translational Research (Adv. Mater. 17/2020). Issue 17 (27th April 2020) - Schiavone, Giuseppe; Fallegger, Florian; Kang, Xiaoyang; Barra, Beatrice; Vachicouras, Nicolas; Roussinova, Evgenia; Furfaro, Ivan; Jiguet, Sébastien; Seáñez, Ismael; Borgognon, Simon; Rowald, Andreas; Li, Qin; et al.
Abstract : In article 1906512, Stéphanie P. Lacour and co‐workers propose an experimental framework to advance the translation of soft, implantable bioelectronic interfaces toward medical research and use. A biomimetic in vitro multimodal platform captures the dynamic biophysical environment and replicates in vivo function of the soft implant to fast‐forward its validation toward therapeutical use.